THE INFLUENCE OF PRICE AND ACCESSIBILITY TO NOVEL REQUIREMENT IN TOGAMAS BOOK STORES - Zulganef; Nina HerdaUtiari; DewiSyamrohSopiah; FebiAprilliani; Yoga Gunawan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This study aims to determine the influence of price and accessibility on novel loyalty in Togamas bookstores. The population used in this research is TogamasSupratman consumers. The data were collected using a survey method and the type of data was a cross section with a total sample of 121 respondents. The method used in this research is explanatory. The results of the analysis and discussion show that the accessibility variable does not play a role in increasing buyer loyalty. It means that the accessibility variable does not affect loyalty because the effect is not significant (significant value 0.076> 0.05). Meanwhile, the price variable has a significant effect, (significance value 0.000 <005). Thus, it can be concluded that the variable that has influenced loyalty in purchasing novels at the Toga Mas bookstore so far is the price variable. Meanwhile, the accessibility of Toga Mas bookstore does not affect consumer loyalty